Outcomes after Decompressive Craniectomies In Middle Cerebral Artery Infarctsa In a new Neurosurgical Unit - Ahmad Sukari, Aiman Asyraf; Bohari, Muhammad Hafiz; Haron, Rahmat (Journal Of Cardiovascular, Neurovascular & Stroke, 2021)
Background: Due to lack of thrombolytic therapy in our center, decompressive craniectomy is offered to patients for treatment for middle cerebral artery (MCA) infarcts. The aim of the study is to review the mortality and morbidity outcomes of patients with MCA infarct who undergo surgery at our center. Methods: From August 2016 until December 2017, 29 patients underwent decompressive craniectomy for MCA infarct. Patients were evaluated based on their demographics, and patient risk factors including diabetes, hypertension, cardiac disease, renal problems and pneumonia. Clinical neurological presentation was evaluated with Glasgow Coma scale (GCS). Patient outcome was evaluated with mortality within 1 month and modified Rankin Scale score in 6 months. Results: Mortality was 41% (12 patients) during 30 days and good functional outcome (mRS 3 or less) in surviving patients was achieved by 47% (8 patients) at 6 months. The factors associated with higher mortality were low preoperative GCS score (p-value 0.025 at CI 95%), impaired renal function (p-value 0.011 at CI 95%) and preexisting cardiac problems (p-value 0.003 at CI 95%). Although the odds of 30-day mortality was higher in the above 60 age group, it did not reach statistical significance (p-value 0.422 at 95% CI). However, no preoperative factors available had any association with outcome at 6 months. Conclusion: Preoperative GCS, renal function and preexisting cardiac problems should be considered during patient selection for surgery for MCA infarct. Age may have a lesser role in determining mortality. However, 6 month outcome is unpredictable and should be highlighted to family members when offering surgery for these patients